Why do people use a mobile wallet? The case of fintech companies in Jordan - Ohoud Khasawneh; Rana AlBahsh (Investment Management & Financial Innovations)
Understanding consumer intentions regarding mobile wallet (m-wallet) adoption is paramount in the mobile commerce landscape, particularly in cash-centric economies like Jordan. Despite efforts to shift toward digital payments, cash transactions remain prevalent, highlighting the need to explore m-wallet service adoption dynamics in Jordan.This study aims to identify the factors influencing Jordanian consumers’ adoption of m-wallet services, focusing on the motivations and barriers. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT2) as a theoretical foundation, the research integrates various models to assess technology acceptance. A questionnaire distributed among m-wallet users from fintech companies in Jordan garnered 421 responses, analyzed using the Smart PLS 3 software.The findings indicate a positive impact of all variables on the propensity for m-wallet adoption in Jordan. Notably, perceived usefulness, ease of use, and facilitating conditions significantly influenced user decisions, evidenced by R-square values of 0.78%, 0.758% and 0.684%, respectively. Meanwhile, perceived value, security, privacy, and social influence had a moderate effect. The attractiveness of alternatives and attitudes towards m-wallet usage showed lesser impact, with R-square values at 26.7% and 22.8%, respectively, illustrating varied influences on adoption rates in determining consumer adoption of m-wallet services in Jordan.This paper enhances research on mobile commerce in developing economies, focusing on Jordan. It explores the adoption of m-wallet services by fintech users, presenting a detailed model. The study provides valuable insights for advancing digital payment systems in this region.